Effect of Service Excellence on Customer Loyalty of Bank Syariah Indonesia (BSI) in Bandar Lampung City with Customer Satisfaction as an Intervening Variable - Lukman Firnanda; Ujang Hanif Mustofa; Anas Malik (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of Service Excellence on customer loyalty with customer satisfaction as an intervening variable in Bank Syariah Indonesia in Bandar Lampung. The method used is quantitative with Partial Least Square-Structural Equation Modeling (PLS-SEM) approach through SmartPLS software. The results showed that Service Excellence has a positive and significant effect on customer loyalty and customer satisfaction. In addition, Customer Satisfaction also has a significant effect on customer loyalty. However, the indirect effect of Service Excellence on customer loyalty through customer satisfaction is not significant, so mediation is not proven. This finding confirms the importance of excellent service in improving customer loyalty directly